Experimental Demonstration of multiple Disaggregated OLTs with Virtualised Multi Tenant DBA, over General Purpose Processor - Ruffini, Marco (My University, 2020)
We demonstrate an Optical Line Terminal with fully softwarised data plane and virtual Dynamic Bandwidth Allocation in a sliceable, multi-tenant PON architecture. We evaluate performance results for 6 OLTs sharing the same general purpose processor.
Optical Fibre Communications (OFC)
PUBLISHED
Keywords: Passive optical networks; Optical line terminal; 5G networks